Diode Laser Ablation of Prostate and Channel Transurethral Resection of Prostate in Patients with Prostate Cancer and Bladder Outlet Obstruction Symptoms - Javanmard, Babak; Hassanzadeh Haddad, Amin; Yaghoobi, Mohammad; Lotfi, Behzad aser application in medical sciences res (Urology Journal, 2014)
Purpose: To evaluate the efficacy of diode laser ablation of prostate for treating lower urinary tract symptoms (LUTS) in patients with locally advanced prostate cancer and comparing results with palliative transurethral resection of prostate (pTURP). Materials and Methods: Thirty-six known cases of locally advanced prostate cancer with a maximum urinary flow rate (Qmax) of 12 mL per second or less and an International Prostate Symptom Score (IPSS) of 20 or more were included in this study. Patients were randomized into two groups. The first group underwent pTURP and for the second group diode laser ablation of prostate was done. In 6 months post-operative follow up, patients were evaluated for IPSS, post void residual (PVR) urine volume, Qmax and possible complications such as urethral stricture or urinary incontinence. Results: Postoperatively, mean IPSS was 11.1 ± 4.1 in TURP group and 11.7 ± 3.6 in laser group (P = .64). Mean PVR was 18.4 ± 3.5 mL in TURP group and 17.7 ± 6.3 mL in laser group (P = .68). Mean Qmax in TURP and laser groups were measured 20.1 ± 4.5 mL/s and 19.4 ± 2.6 mL/s, respectively (P = .57). While there was a significant improvement in IPSS and Qmax and PVR in both groups, statistical analysis did not show any significant difference postoperatively between pTURP and laser groups. Conclusion: Diode laser ablation of prostate and pTURP, both improved significantly IPSS, PVR and Qmax. But hospital stay and post-operative catheterization time was less in laser group.